1 World Manga : Passage 5. Girl's Education - Life Lessons - Roman, Annette (San Francisco: VIZ Media and World Bank, 2012)
The first World Manga series offers a premise where the hero must grapple with social problems of a global magnitude that are set in the real world. Fifteen year-old orphan Rei survives by his wits and guts on the mean streets of the world. His fortunes take a strange turn when he meets a trainer wielding some powerful transformational magic who offers to coach him to achieve his dream of becoming the greatest marital artist in the world! But it seems Rei's trainer is more interested in developing his mind, spirit and ugh! Heart than his thrashing, raging, and fighting moves! The stakes get higher when Rei meets a young woman fighting just to survive! Can Rei meets vanquish the specter of poverty? This publication includes some of the following headings: poverty - a ray of light; HIV/AIDS - first love; child soldiers of boys and men; global warming - the lagoon of the vanishing fish; girl's education - life lessons; corruption - broken trust; and interview with the author of the first World Bank Manga (passage one to passage six).